2006
DOI: 10.1128/mcb.02141-05
|View full text |Cite
|
Sign up to set email alerts
|

An ATR- and BRCA1-Mediated Fanconi Anemia Pathway Is Required for Activating the G2/M Checkpoint and DNA Damage Repair upon Rereplication

Abstract: The timely assembly of prereplicative complexes at replication origins is tightly controlled to ensure that genomic DNA is replicated once per cell cycle. The loss of geminin, a DNA replication inhibitor, causes rereplication that activates a G 2 /M checkpoint in human cancer cells. Fanconi anemia (FA) is an autosomal recessive and X-linked disorder associated with cancer susceptibility. Here we show that rereplication activates the FA pathway both for the activation of a G 2 /M checkpoint and for repair proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
93
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 52 publications
9
93
1
3
Order By: Relevance
“…This Chk2-and p53-independent cell death pathway is probably similar to the one that mediates a delayed cell death in chk2 and p53 mutants after ionizing radiation, although further experiments will be required to define this pathway (Wichmann et al 2006). Our results in Drosophila are similar to those from human cells in culture, in which Cdt1 misexpression induces p53-dependent apoptosis, suggesting that the rereplication checkpoint response is conserved (Vaziri et al 2003;Zhu and Dutta 2006).…”
Section: Rereplication Induces Apoptosis In Drosophilasupporting
confidence: 77%
See 1 more Smart Citation
“…This Chk2-and p53-independent cell death pathway is probably similar to the one that mediates a delayed cell death in chk2 and p53 mutants after ionizing radiation, although further experiments will be required to define this pathway (Wichmann et al 2006). Our results in Drosophila are similar to those from human cells in culture, in which Cdt1 misexpression induces p53-dependent apoptosis, suggesting that the rereplication checkpoint response is conserved (Vaziri et al 2003;Zhu and Dutta 2006).…”
Section: Rereplication Induces Apoptosis In Drosophilasupporting
confidence: 77%
“…In addition, multicellular eukaryotes express another important inhibitor of pre-RC reassembly, Geminin, which binds Cdt1 and prevents it from reloading the MCM complex after origins initiate (McGarry and Kirschner 1998;Wohlschlegel et al 2000;Tada 2007). In human cells, increased Cdt1 results in DNA rereplication and DNA damage that activates a G2/M checkpoint arrest, mediated by the Fanconia anemia checkpoint proteins (FANC), or apoptosis mediated by p53 (Melixetian et al 2004;Zhu et al 2004;Zhu and Dutta 2006). Cdt1 is up-regulated in several human cancers, and misexpression of Cdt1 in T cells of p53 mutant mice results in aneuploidy and a highly penetrant lymphoma, consistent with other evidence that the DNA damage caused by rereplication can lead to genome instability and oncogenesis if checkpoints fail (Hook et al 2007).…”
mentioning
confidence: 99%
“…Mitotic catastrophe is a term used to describe these failures in mitosis, reported previously in literature (3, 12 -15). Accumulating evidence has implicated Brca1 as a key regulator of the DNA damage checkpoint response, the S and G 2 -M checkpoint (16). Studies by Yarden et al (17) show that Brca1 is necessary to activate chek1-induced DNA damage G 2 -M arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of exogenous DNA-damaging agents, deregulated expression of CDT1 causes profound cell cycle defects. Overexpression of CDT1 or the depletion of geminin causes overt rereplication (as evidenced by >4N cells), DNA damage, and the subsequent activation of a prolonged G2/M checkpoint (Vaziri et al 2003;Melixetian et al 2004;Zhu and Dutta 2006).…”
mentioning
confidence: 99%
“…The second pathway requires FANC proteins (FANC-C and FANC-D2) and leads to the downregulation of active CyclinB/CDC2 kinase through unknown mechanisms (Freie et al 2004). Molecular studies have demonstrated that rereplication triggers prolonged G2 arrest through activation of the p53 or FANC pathways (Vaziri et al 2003;Zhu and Dutta 2006).…”
mentioning
confidence: 99%